A Bio-medical Informatics Perspective on Human Factors - Meyer, R.; Section Editor for the IMIA Yearbook Section on Human Factors (Yearbook of Medical Informatics, 2010)
Objectives: to select and summarize excellent research papers published in 2009 in the field of human factors in bio-medical informatics.Methods: we attempt to derive a synthetic overview of the activity and new trends in this field, from a selection of research papers published in 2009.Results: it is possible to identify commonalities in this diverse domain: healthcare information technologies (HIT) adoption still occupies a central role in the fieldwith research focused mainly on measuring impact and influence of this adoption.Conclusion: The HIT community is giving birth to interdisciplinary research and clear methods to optimize implementation and subsequent achievement of managerial objectives. It also tries to synthesize the major findings in workshops, meetings and networks. The best paper selection of articles on human factors shows examples of excellent research on methods concerning original options to assess the importance of healthcare personnel psycho-sociology when confronted to the adoption of new tools and process which still does not prevent failures but will help learning from them.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; human factors